Avian/Bird flu: A review: H5N1 outbreaks in Nepal - Shrestha, Dhiraj; Bhattachan, Balkrishna; Parajuli, Hiramani; Shrestha, Sujata (Nepal Journal of Biotechnology, 2021)
Avian/Bird flu is a viral disease of birds, caused by avian influenza virus (AIV). A highly pathogenic avian influenza (HPAI) H5N1 has breached the barrier of species to humans and other animals escalating the pandemic threat. If the H5N1 evolves to a human-to-human transmissible virus retaining its pathogenicity, it can trigger an influenza pandemic. H5N1 has a mortality rate of about 60%, varying with strains. Meaningful antigenic alteration in hemagglutinin (HA) and/or neuraminidase (NA) results in recurring pandemics. The HPAI H5N1 subtype alone has outreached more than 77 nations around the world since the first human case and death was reported in 1997. Wild and migratory birds are the AIV reservoirs. Poultry is primarily impacted by incidents and outbreaks of the disease. A wide range of serological and molecular methods have substantially aided in the identification of bird flu in humans. Candidate vaccines have been developed, yet are not ready for widespread use. Oseltamivir (brand name: Tamiflu) is the preferred drug for the management of human Influenza-like illness (ILI). Surveillance, mass awareness, and pandemic preparedness abiding WHO recommendations are of paramount importance for the prevention of bird flu outbreaks.